The World of Spore readers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Celebrating a magazine s share in the agriculture of Africa, Caribbean and the PacificIn the countries of Africa, the Caribbean and the Pacific, as elsewhere, agriculture is central to the lives of all people. As the prime source of food and...